ANALISIS WACANA FEMINIS MENGENAI HUMAN TRAFFICKING DALAM FILM JAMILA DAN SANG PRESIDEN - Diah Handayani (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2015)
Human trafficking is one of the problems that still cannot be resolved in Indonesia. In general, there are still many problems from patterns of prevention and crime controlling of human trafficking which is currently being implemented. The movie of ‘Jamila and the President’ is a representation of a survey result conducted by a filmmaker who cares about women problems in this country, namely Ratna Sarumpaet. This research was developed from critical discourse analysis models by Sara Mills. The result showed that there was an impartiality of the state's role to a female victim of human trafficking which affects the moral aspect, gender, and the so many cases of human trafficking. The contribution of this study is to give knowledge and awareness of women to fight and or without someone’s help in order to fix their condition to be better.